Peran Organisasi 'Aisyiyah Dalam Mewujudkan Keluarga Sakinah di Indonesia - Christian, Yogi; Muhammad Sholeh Marsudi (Counselle| Journal of Islamic Guidance and Counseling, 2025)
The family is the main foundation in society for the formation of individual character, the ideal family in Islam is a family embedded in love, affection and tranquility. In 2024 Indonesia showed a significant trend in divorce cases, in this case the 'Aisyiyah organization plays an important role in the realization of a sakinah family in Indonesia. The purpose of this study is to determine how the concept of a sakinah family in the perspective of the 'Aisyiyah organization and how the role of the 'Aisyiyah organization in realizing a sakinah family in Indonesia. This research model uses qualitative research with the type of library research (literature study). The results of this study indicate that the 'Aisyiyah organization plays an important role in realizing and fostering a sakinah family in Indonesia as evidenced by the main idea related to the guidance program towards a sakinah family starting in 1989 until now. The sakinah family in 'Aisyiyah's perspective has been explained in detail through “Dinamika 'Aisyiyah Gerakan Qaryah Thayyibah dan Keluarga Sakinah ”.